How Racial/Ethnic Diversity in Urban Schools Shapes Intergroup Relations and Well-Being: Unpacking Intersectionality and Multiple Identities Perspectives - Ghavami, Negin; Kogachi, Kara; Graham, Sandra (Frontiers in Psychology, 2020)
Today’s urban schools provide a unique intergroup context in which the students vary not only by race/ethnicity but also by the relative representation of their racial/ethnic groups. In two studies, we examined how this diversity aligns with intersectionality and multiple identities perspectives to affect the power and status associated with each group to shape intergroup dynamics. Study 1 focused on the perception of intergroup bias to investigate how perceived presence of same-race/ethnicity peers affects middle school students’ intersectional intergroup attitudes based on race/ethnicity, gender, and sexual orientation. Middle school students (N=1,107; Mage = 12.10; SD = .99) were randomly assigned to view Facebook-like profiles of peers that varied by gender (boy, girl), race/ethnicity (African American, Latinx), and sexual orientation (straight, lesbian, gay) and offered their first impressions as a way to assess various domains of intergroup attitudes. The perceived presence of same-race/ethnicity peers influenced intersectional intergroup attitudes, however, differentially so depending on stereotypes, prejudice, and behavioral tendencies. Study 2 focused on the experience of intergroup bias and simultaneously examined race, gender, and weight discrimination and its consequences among middle school students (N=4,172; Mage = 13.5; SD = .87). Using latent profile analysis, five profiles of youth based on the pattern of perceived discrimination due to gender, race/ethnicity, and weight were identified. Being African American, Latinx, and male with a high body mass index (BMI) and few same-race/ethnicity peers at school predicted membership in a race profile, whereas being White or Asian with high BMI and more same-race/ethnicity peers predicted membership in a weight profile. Perceiving oneself as gender atypical was associated with all discrimination profiles.